POTENSI TEPUNG CEKER DAN LEHER AYAM SEBAGAI FOOD INGREDIENT DAN SUMBER PANGAN FUNGSIONAL - Rita Purwasih; Wiwik Endah Rahayu (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Chicken feet and neck bones flour are the products of live stock which have a high protein and mineral content. However, they have not been utilized functionally, while they have a potential as a food ingredient and functional food source. Therefore, it is necessary to make efforts to utilize the chicken feet and neck bones flour as functional food products and new food ingredients. Both chicken feet and neck bones flour can be mixed with other raw materials which have a potential function as food sources for energy. The addition of protein and minerals from the both chicken feet and neck bones flour are expected to be able to increase the nutritional value of a product, especially for the protein and mineral content. Thus, the product is not only as an energy source but also as a source of protein and minerals. Moreover, functional food development is not only beneficial for consumers but also as an opportunity for the food industry and government